Revolutionizing Society through Pancasila-Based Legal Education with Street Law (Case of Indonesia) - Ridwan Arifin; Bayangsari Wedhatami; Riska Alkadri; Ridoan Karim; Fraz Ashraf Khan (The Indonesian Journal of International Clinical Legal Education, 2023)
This paper explores the revolutionary impact of integrating Pancasila-based legal education with the Street Law model on Indonesian society. Pancasila, Indonesia's foundational philosophy, serves as a guiding framework for legal education, while the Street Law model provides a practical, experiential learning approach. Through a meticulous case study focused on Indonesia, the research investigates the nuanced ways in which this innovative educational combination contributes to transformative societal changes. The study analyzes the influence of Pancasila-inspired legal education on shaping societal norms, values, and fostering legal awareness. By delving into specific instances and outcomes within the Indonesian context, the research illuminates how this integrated approach cultivates a deeper understanding of legal principles and ethical considerations among the populace. The findings not only highlight the success of this educational model in enhancing legal knowledge but also underscore its broader impact on social dynamics. This paper contributes valuable insights into the potential of Pancasila-based legal education with the Street Law model to revolutionize traditional legal teaching methods and, in turn, foster positive societal advancements within the unique cultural and legal landscape of Indonesia.